Analysis Of The Quality Growth Index In Syria During The Period 1995-2010 - قابقلي, ابتهال (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Economic growth is one of the basic goals pursued by governments and aspired by the people, because it represents the material recapitulation of economic and non-economic efforts in society. It is one of the necessary conditions to improve the standard of living of societies and translate strong growth into better living conditions. Policy makers in developing economies, many of which have experienced strong economic growth in the past decade. However, the indicators of poverty, inequality and unemployment remain high. High growth alone will not improve social conditions. Therefore, the quality of growth index has been studied. This indicator deals with economic and social aspects to give a more accurate picture of the situation of economic and social situation of countries economy.